IMPLEMENTASI PENDIDIKAN AKHLAK DALAM MEMBENTUK KEPRIBADIAN MUSLIM SISWA DI MADRASAH ALIYAH PONDOK PESANTREN HIDAYATULLAH TANJUNG MORAWA - Muflihaini Muflihaini (Pascasarjana UIN Sumatera Utara, 2017)
Abstrct: This study aims to (1) know the moral education program in shaping the Muslim personalityof the students (2) to know the implementation of moral education in shaping the Muslim personalityof the student (3) to know whether moral education can shape the student’s muslim personality (4)know the supporting factors and obstacles in the implementation Moral education students. Thisresearch uses qualitative approach. The research was conducted at Private Madrasah Aliyah (MAS)Pondok Pesantren Hidayatullah Tanjung Morawa. The data sources of this research are sources, data,and documents. The research data was collected through observation, interview, and document analysis.Research data using data reduction techniques, data presentation and conclusions. School environmentas well as in the classroom. The research informants consisted of the chairman of the foundation,principals, teachers and students. The object of research is the implementation of moral education inshaping the student’s muslim personality. Research instruments are interview guides, observation sheets,and field notes. Data analysis with qualitative descriptive method.